Bahasa Inggris Bisnis dari Perspektif Alumni Jurusan Akuntansi Politeknik Negeri Padang - Martini Martini (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2015)
As a part of dissertaion research entitled “Developing A Model Of Business English Teaching Material For Students Of Politeknik Negeri Padang”. This article tells about the needs of Business English in workplaces from the graduate students persperctive. The information gottten can be used as inputs is designing Business English curriculum which in based on Link and Match concept between the needs of workplaces and educational institutions. A survey was done by spreading online questionnaires by using Google drive to the graduates of accounting department, who work for some companies in Indonesia. By using descriptive analysis, finding of the research obtains an overview that four language skills (speaking, listening, reading, and writing) are very impportant in business communication. It menas that they must be taught in Business English class. Next, it is also obtained that grammar, vocabulary, pronounciation, and translation are also very important to be taughy. Besides, this study can determine some business topics that are needed for Business English class.